1990
DOI: 10.1017/s0021859600074001
|View full text |Cite
|
Sign up to set email alerts
|

Whole-body and tissue protein synthesis in steers losing weight on a low-protein roughage diet: the effect of trenbolone acetate

Abstract: S U M M A R YSix Brahman (Bos indicus) steers implanted with 300 mg trenbolone acetate and six similar nonimplanted steers were fed a low-quality, low-protein roughage diet at 10 g dry matter/kg live weight. They were housed in individual pens for 27 days in 1987 before being placed in metabolism crates for measurement of digestibility, nitrogen retention, and the rate of protein synthesis in the whole body and fractional rate in three muscles and hide.The rate of weight loss of steers treated with trenbolone … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1992
1992
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…Testosterone and estradiol were shown to have no effect on muscle cellular protein synthesis or degradation (Roeder et al, 1986;Desler et al, 1996), whereas Martinez et al (1984) and Hayden et al (1992) showed that testosterone and trenbolone acetate increased protein synthesis only. Conversely, Hunter and Magner (1990) found trenbolone acetate decreased protein degradation. In general, our results agree with the body of literature that trenbolone acetate had its strongest effect on protein synthesis and not protein degradation.…”
Section: Discussionmentioning
confidence: 93%
“…Testosterone and estradiol were shown to have no effect on muscle cellular protein synthesis or degradation (Roeder et al, 1986;Desler et al, 1996), whereas Martinez et al (1984) and Hayden et al (1992) showed that testosterone and trenbolone acetate increased protein synthesis only. Conversely, Hunter and Magner (1990) found trenbolone acetate decreased protein degradation. In general, our results agree with the body of literature that trenbolone acetate had its strongest effect on protein synthesis and not protein degradation.…”
Section: Discussionmentioning
confidence: 93%
“…A set of 25 publications including 624 observations were found in the literature (Buttery et al, 1975;Lobley et al, 1980;Davis et al, 1981;Bryant and Smith, 1982a, b;Sinnett-Smith et al, 1983;Schaefer et al, 1986;Bohorov et al, 1987;Attaix et al, 1988a, b;Early et al, 1988; Abdul-Razzaq and Bickerstaffe, 1989;Eisemann et al, 1989;Champredon et al, 1990;Early et al, 1990;Hunter and Magner, 1990;Lobley et al, 1990;Baracos et al, 1991;Attaix et al, 1992;Harris et al, 1992;Lobley et al, 1992;Southorn et al, 1992;Crompton and Lomax, 1993;Lobley et al, 1994;Tauveron et al, 1994 (France et al, 1988 (Tomassone et al, 1992 (France et al, 1988). However, this compartment has a short half-life of between 2 and 5 s (Martin et al, 1977) .…”
Section: Methodsmentioning
confidence: 99%
“…Locally produced IGF-I in skeletal muscle is able to progress bovine satellite cells through proliferation and differentiation into skeletal muscle fibres. This results in increased protein synthesis and decreased protein degradation (Vernon and Buttery 1978;Lobley et al 1985;Hunter and Magner 1990). Moreover, it allows for maintenance of the DNA to protein ratio throughout skeletal muscle hypertrophy.…”
Section: Biological Alterations Post-administrationmentioning
confidence: 99%